2015
DOI: 10.1037/abn0000060
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco withdrawal symptoms mediate motivation to reinstate smoking during abstinence.

Abstract: Withdrawal-based theories of addiction hypothesize that motivation to reinstate drug use following acute abstinence is mediated by withdrawal symptoms. Experimental tests of this hypothesis in the tobacco literature are scant and may be subject to methodological limitations. This study utilized a robust within-subject laboratory experimental design to investigate the extent to which composite tobacco withdrawal symptomatology level and three unique withdrawal components (i.e., low positive affect, negative aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 52 publications
4
45
1
Order By: Relevance
“…Part of these findings is in accord with a previous clinical report that craving mediated the relation between depressive symptoms and relapse rates among substance users (Witkiewitz and Bowen 2010). The present results are also congruent with findings that high-arousal NA subtypes (e.g., anger and anxiety) versus low-arousal NAs (e.g., depression) appears to be stronger mediators of the relation of abstinence and reinstatement of smoking in laboratory settings (Aguirre et al 2015). Future research should continue to examine likely differences among the subtypes of affective symptoms with respect to their direct and/or indirect impact on relapse risks.…”
Section: Discussionsupporting
confidence: 90%
“…Part of these findings is in accord with a previous clinical report that craving mediated the relation between depressive symptoms and relapse rates among substance users (Witkiewitz and Bowen 2010). The present results are also congruent with findings that high-arousal NA subtypes (e.g., anger and anxiety) versus low-arousal NAs (e.g., depression) appears to be stronger mediators of the relation of abstinence and reinstatement of smoking in laboratory settings (Aguirre et al 2015). Future research should continue to examine likely differences among the subtypes of affective symptoms with respect to their direct and/or indirect impact on relapse risks.…”
Section: Discussionsupporting
confidence: 90%
“…This failure to support habit theory was found in both clinical (tests 5-8) and non-clinical samples (1)(2)(3)(4). Furthermore, the failure to support habit theory cannot be attributed to the use of concurrent choice procedures (which tend to discourage habitual learning as noted earlier) because all of the tests in Table 2 used concurrent choice procedures, both those that failed (test [1][2][3][4][5][6][7][8] and those that notionally supported habit theory (test 9-11).…”
Section: Human Studiesmentioning
confidence: 80%
“…The self-medication account specifies psychiatric symptoms, which increase during abstinence, as the main driver of persistent drug use [5]. Although individual sensitivity to a multidimensional withdrawal syndrome and other negative states is associated with problematic substance use, there remains debate as to which component of withdrawal is most important [6], how this relates to psychiatric comorbidity [7,8], and whether negative states prime drug seeking automatically [9] or via value-based decision making [10,11]. This work forms the basis of the goal-directed choice under negative affect account evaluated at length later.…”
Section: Brief Introduction To Theories Of Addictionmentioning
confidence: 99%
“…The study demonstrated sensitivities in clinical depression which had previously only been associated with sub-clinical depression and hedonic traits (Audrain-McGovern et al, 2014; Cook et al, 2004; Fucito and Juliano, 2009; Leventhal et al, 2013; Leventhal et al, 2014; Leventhal et al, 2009; Perkins et al, 2010). As individual differences in sensitivity to negative mood/stress induced craving (Back et al, 2010; Brady et al, 2006; Cooney et al, 1997; Higley et al, 2011; Sinha et al, 2011; Sinha et al, 2006) and abstinence induced craving (Aguirre et al, 2015; Ferguson et al, 2006; McCarthy et al, 2008; Piper et al, 2008; Zuo et al, 2016) predict a higher risk of relapse, these sensitivities arguably underpin dependence, persistence and relapse, and should be targeted to improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%